The Intermetalloid Clusters [Ni2Bi12]4+and [Rh2Bi12]4+– Ionothermal Synthesis, Crystal Structures, and Chemical Bonding - Groh, Matthias F.; Mueller, Ulrike; Isaeva, Anna; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2019)
The intermetalloid clusters [M 2 Bi 12 ] 4+ (M = Ni, Rh) were synthesized as halogenido-aluminates in Lewis-acidic ionic liquids. The reaction of bismuth and NiCl 2 in [BMIm]Cl·5AlCl 3 (BMIm = 1-butyl-3-methylimidazolium) at 180 °C yielded black, triclinic (P1) crystals of [Ni 2 Bi 12 ][AlCl 4 ] 3 [Al 2 Cl 7 ]. Black, monoclinic (P2 1 /m) crystals of [Rh 2 Bi 12 ][AlBr 4 ] 4 precipitated after dissolving the cluster salt Bi 12–x RhX 13–x (X = Cl, Br; 0 < x < 1) in [BMIm]Br·4.1AlBr 3 at 140 °C. In the cationic cluster [Ni 2 Bi 12 ] 4+ , the nickel atoms center two base-sharing square antiprisms of bismuth atoms (symmetry close to D 4h ). The valence-electron-poorer rhodium-containing cluster is a distorted variant of this motif: the terminating Bi 4 rings are folded to bicyclic “butterflies“ and the central square splits into two dumbbells (symmetry close to D 2h ). DFT-based calculations and real-space bonding analyses place the intermetalloid units between a triple-decker complex and a conjoined Wade-Mingos cluster.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Bismuth; Cluster compounds; Coordination compounds; Ionic liquids; Transition metals